Owning solutions: A collaborative model to improve quality in hospital care for Aboriginal Australians - Durey, Angela; Wynaden, Dianne; Thompson, Sandra; Davidson, Patricia; Bessarab, Dawn; Katzenellenbogen, Judith (Blackwell Science, 2011)
Well-documented health disparities between Aboriginal and Torres Strait Islander (hereafter referred to as Aboriginal) and non-Aboriginal Australians are underpinned by complex historical and social factors. The effects of colonisation including racism continue to impact negatively on Aboriginal health outcomes, despite being under-recognised and under-reported. Many Aboriginal people find hospitals unwelcoming and are reluctant to attend for diagnosis and treatment, particularly with few Aboriginal health professionals employed on these facilities. In this paper, scientific literature and reports on Aboriginal health-care, methodology and cross-cultural education are reviewed to inform a collaborative model of hospital-based organisational change. The paper proposes a collaborative model of care to improve health service delivery by building capacity in Aboriginal and non-Aboriginal personnel by recruiting more Aboriginal health professionals, increasing knowledge and skills to establish good relationships between non-Aboriginal care providers and Aboriginal patients and their families, delivering quality care that is respectful of culture and improving Aboriginal health outcomes.A key element of model design, implementation and evaluation is critical reflection on barriers and facilitators to providing respectful and culturally safe quality care at systemic, interpersonal and patient/family-centred levels. Nurses are central to addressing the current state of inequity and are pivotal change agents within the proposed model.